Effet de l'addition des tannins de châtaigniers sur la rétention azotée et la digestibilité chez les ruminants ingérant des produits herbagers - Kriaa, S.; Thewis, A. (Tropicultura, 1999)
The Influence of the Addition of Extract of Chestnut Tannin on the Nitrogen Balance and the Digestibility of Fresh Grass in Ruminant. The use of chestnut tannin (CT) (hydrolysable Tannins), added at a low concentration (4 g CT/100 g of total nitrogen (TN) = 0, 8 g cT/kg of DM distribute) to a grass forage for growing sheep, improves the N retention (P <0, 01). The improvement of N retention is explained by the decrease of nitrogen in the urine, indicating a better use of absorbed nitrogen. Moreover, the addition at these low concentrations of CT to fresh grass does not alter neither the digestibility of its constituents (OM, TN, ADF) nor the rate of ingestion.